Governing by Checkpoints: Everyday Mobility and Control in Wartime Amhara - Rediet Adane Derebe (Kulturní Studia)
This article examines the everyday governance of mobility in the conflict-affected Amhara region of northern Ethiopia. In a fragmented and militarised landscape, checkpoints—erected by state forces, paramilitary groups such as Fano, and informal actors—have emerged as the dominant infrastructure of rule. Drawing on original fieldwork conducted in March 2025, the article explores how individuals navigate a fluid terrain of ad hoc control, where power is enacted not through institutions but through glances, silences, and bodily performances. Through the lens of “vernacular governance by passage,” the study reveals how movement becomes both a site of vulnerability and a modality of political negotiation. Theoretically, the article contributes to debates on fragmented sovereignty, affective governance, and the embodied dimensions of state power. It argues that governance in Amhara has not collapsed, but has migrated into movement itself—where checkpoints are not merely barriers but stages upon which authority is improvised, contested, and endured.